Marcadores do estresse oxidativo em crianças e adolescentes infectados com Helicobacter pylori residentes de uma comunidade urbana no Nordeste do Brasil - Oliveira, Michelle Soeiro de (2017)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium that colonizes the human stomach being acquired during childhood. Chronic inflammation induced by the bacterium can lead to changes in DNA, resulting in increased production of Reactive Oxygen Species (ROS). The aim of this study was to evaluate the serum levels of malondialdehyde (MDA), glutathione (GSH), catalase, nitric oxide nitrate and nitrite (NO) and myeloperoxidase (MPO) in children and young infected and not infected with H. pylori. Materials and methods. A descriptive and cross-sectional study was carried out at the University Park community in Fortaleza, CE, including 143 individuals from the community, aged between 8 and 18 years, mean ± 14.16 years and standard deviation of ± 3.85. , 48.5% (65/134) of the male gender and 51.4% (69/134) of the female sex. Interviews were conducted to collect epidemiological data from these individuals and blood samples were collected and centrifuged and the serum was collected and stored in a freezer at -80 ° C. The detection of H. pylori was performed by means of the Carbon-13-labeled Urea Respiratory Test. Serum dosages were performed on a microplate reader for MDA, GSH, NO and MPO, and catalase was determined by Spectrophotometry. Results. Of the 134 individuals studied, 59.7% (80/134) were H. pylori positive and 40.2% (54/134) negative, there was no significant difference between H. pylori positive and negative individuals with respect to gender (p = 0,161) or age group (p = 0.647). Statistical significance was not observed between H. pylori (+) and (-) patients in relation to serum levels of GSH-Rd (92.3 ± 117.6 and 75.4 ± 90.6, p = 0.363), and MPO (3.22 ± 3.61 and 4.44 ± 5.16, p = 0.295) respectively. On the other hand, the infected group had higher serum levels of MDA (0.49 ± 0.3964 and 0.27 ± 0.19 and p = 0.001), Catalase (2.72 ± 2.90 and 1.69 ± 1 , 88, p = 0.010) and reduction of nitric oxide (0.111 ± 0.00 and 0.115 ± 0.01, p = 0.001). Therefore, infection caused by H. pylori is associated with increased levels of MDA and catalase and reduced levels of nitric oxide when compared to uninfected individuals.